PENGARUH MODEL PEMBELAJARAN RME BERBANTUAN VIDEO BERNUANSA ETNOMATEMATIKA TERHADAP KEMAMPUAN LITERASI MATEMATIS KELAS II - binti Hamdan, Syafiqah Putri Nabila; Tamba, Robenhart (Universitas Negeri Medan, 2024)
This research is motivated by several facts in the field which show that students' ability to understand mathematical concepts is still low. The aim of this research is to determine whether or not there is an influence of the RME learning model with the help of ethnomathematics nuanced videos on students' mathematical literacy abilities. This research is experimental research with a factorial experiment design. The data collection techniques used in this research are tests, observation and documentation. Meanwhile, the data analysis technique used is the two-way ANOVA test. Based on the results of data analysis, it can be concluded that 1) There is a difference in the ability to understand mathematical concepts between students who study using the Realistic Mathematic Education learning model with the help of learning videos and students who study directly using the lecture method. Thus, in general it can be concluded that the Realistic Mathematic Education (RME) learning approach with the help of ethnomathematics nuanced videos has an effect on students' mathematical literacy abilities in terms of student learning outcomes. Keywords: Realistic Mathematic Education, Ethnomathematics, Mathematical Literacy.